POSTPARTUM CARE ACCORDING TO SUNDANESE CULTURE IN WERU VILLAGE SUKARESMI DISTRICT, PANDEGLANG REGENCY - ISMI YAUMIL RACHMAH; RISZA CHOIRUNISSA; RETNO WIDOWATI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
Maternal deaths often occur during labor and early postpartum. Pandeglang Regency is one of the areas that still carry out many traditional care traditions by utilizing herbal ingredients and other traditions that have long been carried out by ancestors from generation to generation during the early postpartum period. To obtain an overview of the traditions carried out by postpartum mothers in Weru Village, Sukaresmi District, Pandeglang Regency. This study uses a qualitative method. The informants in this study were postpartum mothers, midwives and parajis . The instrument in this study used an interview guide. Data collection techniques through in-depth interviews. The tradition that is still followed by mothers in postpartum care is eating raw kencur , using koneng bodas ( temulawak ), drinking herbal medicine, body massage, using stagen , not leaving the house, and consuming apples. The ingredients used to make herbal medicine are kencur , turmeric, ginger, betel leaf and temulawak . Tradition is obtained from parents. Midwives know the traditions that mothers do at home but do not carry out further monitoring. Paraji helps postpartum mothers in taking care of the mother, such as massaging the postpartum mother's body and making herbal medicine.